Emerging horizons: A Rainbow Model for the sustainable implementation of Rain Classroom in vocational nursing education - Lina Wang; Peng Li; Jie Li; Mengqi Chen; Shuang Xi Guo; Youcong Zhu; Xiaolei Gao; Cuiping Li; Anna Ma (PLoS ONE, 2025)
Background The COVID-19 pandemic has accelerated several social changes, particularly the shift in education towards online environments. Digital technologies are being extensively used in educational practices, but current research mostly focuses on describing digital teaching practices, with few studies summarising practical experiences and extracting universal principles and patterns. Objective To summarise the practical experience of using Rain Classroom in information technology teaching tools, and to extract universal principles and patterns. Method From July 1 to December 1 2023, eight semi-structured qualitative interviews were conducted with teachers in Hunan, China, who used Rain Classroom for digital teaching. Through multi-level coding, key themes were progressively distilled from interview data, combined with cross-level mapping from the multidimensional perspectives of the Rainbow Framework, ultimately abstracting theoretical principles. Results The convenience, interactivity and diversified learning functions of Rain Classroom’s digital teaching are highlighted in this study. Through the summarisation of practical experience, a theoretical model was established, focusing on Resilience, Adaptability, Inclusivity, Nurturing Continuous Improvement, Balanced Evaluations, Optimal User Experience and Weathering Challenges with Comprehensive Enablers.